Decoupled Power Control With Indepth Analysis of Single-Phase Electric Springs - Wang, Qingsong; Zuo, Wujian; Cheng, Ming; Deng, Fujin; Buja, Giuseppe (IEEE access, 2020)
Electric spring (ES) as a new effective way to solve the power quality issues caused by the uncertainty of wind and photovoltaic (PV) power, has the advantages of small volume, flexible configuration and low cost. Aiming at improving the dynamic responses of the existing power control for ES-2, a new control with in-depth analysis on the decoupling of the active and reactive powers is proposed in this paper. By introducing second order generalized integrator phase locked loop (SOGI-PLL) and fictitious-axis emulator (FAE) into the control algorithm, the virtual orthogonal voltage and current signals were constructed and the mathematic model of ES-2 in the dq axis synchronous rotating reference frame was established. Then, the control system consisting of three closed loops, namely active power loop, current loop and ES voltage loop, is arranged. Among the three loops, a damped proportional resonance (PR) controller is adopted in the ES voltage loop to ensure the accurate control of the output voltage of ES-2. Instead, traditional PI controllers are used for the current and power loops. Finally, the effectiveness of the proposed decoupled power control is validated by both simulation and experimental results.